The effect of initial placement restrictions on refugees' language acquisition in Germany - Felicitas Schikora (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper analyzes the effect of a recently introduced policy reform on participation in integration courses and on certified language proficiency levels among refugees in Germany. The residence rule restricts initial residence for refugees with a permanent residence permit. Given that treatment intensity varies distinctly across states, I utilize this quasi-experiment and apply a difference-in-differences approach. Using an innovative data-set, the IAB-BAMF-SOEP Survey of Refugees, I find that stricter statutory provisions have a positive effect on the probability to complete a language course and on the level of certified language proficiency. The results indicate that this effect is driven partly by spatial mismatch.
Keywords: J15; J60; K37; 330; Migration; Refugees; Language Acquisition; Placement Restriction; Quasi-Experiment